ANALYSIS OF THE APLICATION OF ENVIRONMENTAL COST ACCOUNTING IN WASTE MANAGEMENT AT AISYIYAH ST. KHADIJAH PINRANG HOSPITAL - Albab, Ulil; Hamid, Abdul; Frihatni, Andi Ayu (Institut Agama Islam Negeri Parepare, 2025)
Environmental accounting is a branch of accounting that focuses on recording, managing, and reporting the environmental impacts of a company’s operational activities. This includes information related to the management of costs associated with waste treatment, energy use, and other natural resource consumption. Environmental accounting also plays an important role in ensuring transparency to external stakeholders, such as the government and the public, allowing organizations to demonstrate their commitment to sustainability and compliance with environmental regulations. This study aims to examine the implementation of environmental cost accounting and waste management practices at RSU Aisyiyah St. Khadijah Pinrang. This research employs a descriptive approach with a qualitative research design. Data were collected through three methods: observation, interviews, and documentation. The data analysis techniques used in this study include data reduction, data presentation, and data verification. The findings of this study indicate that RSU Aisyiyah St. Khadijah Pinrang has not yet implemented environmental cost accounting in accordance with the indicators used in this research, which include control costs, prevention costs, cleaning costs, and environmental revenue. However, the hospital’s waste management practices demonstrate good performance and comply with MKLH Regulation No. 16 of 2016. The hospital has managed its waste according to key indicators of waste management, such as the separation of medical and non-medical waste, the separation of infectious and non-infectious waste, clean water management, and staff education related to hospital waste.